POLA PENDAMPINGAN TEKNOLOGI PADA PROGRAM SWASEMBADA DAGING SAPI DAN KERBAU DI KABUPATEN REJANG LEBONG - Zul Efendi; Erpan Ramon (Jurnal Inspirasi Peternakan, 2021)
AbstractÂ In order to meet production targets local beef at 420.3 thousand tons, the Ministry of Agriculture launched the Self-Sufficiency Program Beef (PSDS) in 2014, which consists of five principal program are: the provision of feeder / local beef, increased productivity and the reproducibility of local cattle, cuts prevention productive cows, cows provision, and setting domestic beef stock. In a way the problems encountered in the implementation of the Self-Sufficiency Acceleration Beef and Buffalo namely coordination and technical issues that are often caused by the slow process of technology transfer from the source to the users of technology. The purpose of this study was to determine the response of users to program and produce recommendations for improvement PSDSK implementation of assistance activities at the local level and Farmers. The experiment was conducted in Rejang Lebong for 8 months, starting in January to October 2011. Assessment is done by "desk study ", field surveys, and the preparation of recommendations for improvement pilot project implementation assistance. Model guidance is expected breeder technology innovation is the high intensity level meeting to discuss the technological innovations that accompanied the practice of cattle farming directly with farmers raising cattle mainly technical. Dissemination of information media support technology innovation raise cattle in various forms also need to be added and evenly distribution. Non-technical aspects such as capital support in raising cattle is also an important requirement adoption of a technological innovation by cattle ranchers.Â Keywords: Mentoring, technological innovation, swasembada, cows, buffaloes